Impact of parental migration on oral health outcomes of left-behind school-aged children in Luchuan, southern China - Rongmin Qiu; Yihong Li; Manisha Malla; Junyu Yao; Dan Mo; Neha Dhakal; Hua Huang (BMC, 2018)
Abstract Background With rapid urbanization in China, an increasing number of rural adults have migrated to cities to seek job opportunities, leaving their school-aged children behind. These left-behind children (LBC) without one or both parents usually receive less attention from their caregivers. Whether the parental migration affects the children's oral health is not well understood. This study aimed to explore the differences in dental caries status and oral health-related behaviors between children with different parental migration experiences in a rural area of Southern China. Methods A cross-sectional study was conducted in Luchuan County of Guangxi Province in 2015. A total of 1085 school children aged 8-12 participated in this study. Participants' demographic characteristics, parental migration information, and eating and oral hygiene habits were collected using a self-administered questionnaire. Dental caries of permanent teeth was examined using the decayed, missing, and filled tooth (DMFT) index recommended by the World Health Organization. Dental caries experience and oral health-related behaviors were compared between LBC and non-LBC, as well as children with different experiences of parental migrations. The impact of various parental migration attributes on LBC oral health outcomes was examined by univariate and multivariate analyses. Results Among the school-aged children examined, 60.9% of them were LBC. Only 29.7% of the children brushed their teeth regularly; 86.5% of them did not know what fluoride toothpaste was. Caries prevalence was 51.4% for LBC and 40.8% for non-LBC (p < 0.001). The LBC experienced a greater DMFT mean (1.20 ± 1.59) compared to the non-LBC (0.85 ± 1.30) (p < 0.001). Oral health-related behaviors were not significantly different between LBC and non-LBC. Dental caries experience and oral health-related behaviors were not related to the type or duration of parental migration. Multiple regression analyses showed that parental migration was one of significant predictors of children's caries outcome; LBC had a higher risk to caries than non-LBC (95% CI =1.26, 2.09). Conclusions These findings indicate that parental migration could be a significant risk factor for caries development among 8- to 12-year-old school children in rural China.